Püskürtme çevrimli reaktörde kütle transfer özelliklerinin belirlenmesi - Akbulut, Lalehan (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2012)
Bu çalışma, Çevre Mühendisliği Bölümü'nde kurulan püskürtme çevrimli reaktörün kütle transfer özelliklerinin belirlenmesi amacıyla gerçekleştirilmiştir. Deneylerin amacı hacimsel kütle transfer katsayısı (KLa), gaz tutulma (?), E/V değerlerinin, farklı nozul ucu ve farklı emme tüpleri kullanılarak hesaplanması ve kıyaslanmasıdır. Deneylerde musluk suyu kullanılmıştır.Yüksek hızlı püskürtme çevrimli reaktöre değişik gaz (hava) ve sıvı (musluk suyu) debileri uygulanarak hacimsel kütle transfer katsayısı (KLa) ve gaz tutulma (?) değerleri hesaplanmıştır. KLa ve ? artışı üzerinde hava debisinin, E/V'ye göre daha etkin olduğu bulunmuştur.

This study was carried out in the Environmental Engineering Department with a jet loop reactor in order to determine the mass transfer properties of the system. The aim of these series of experiments was to calculate and compare the KLa, ?, E/V values collected from different nozzle sizes and suction tubes. Tap water was used throughout the studies.The volumetric mass transfer coefficient (KLa) and gas hold-up (?) values were calculated under different gas (air) and liquid (tap water) flowrates applied to the high rate jet loop reactor. The effect of airflow rate on KLa and ? was found to be more influential compared to the E/V values.
Determination of mass transfer characteristics of jet loop reactor
Keywords: Mühendislik Bilimleri; Engineering Sciences; Çevre Mühendisliği